The Study of Worksheets Based on Creative Problem Solving for Biology Subjects - Baiq Fatmawati; Muhammad Khairul Wazni; Novita Husnawati (Jurnal Penelitian Pendidikan IPA, 2021)
Worksheets are indispensable in the learning process because they can help students become more active and provide feedback in learning activities. Higher-order thinking skill-based worksheet is one of the teaching materials that can be used to make students become more active in the learning process because it can train problem-solving skills, critical thinking, and even creative thinking. This aimed at finding out students' ability to solve problems in biological content using creative problem-solving-based worksheets. The research design used was research and development consisting of defines, design, and development. Participants were 12 graders of XI MA Darul Fatihin NW Gerintuk. Data collection used was worksheets using creative problem-solving indicators consisting of Clarify, Ideate, Develop and Implement. Data analysis was conducted to percentage the score that gets 3, 2, and 1. The results of the data analysis showed that 1) Ecosystem Components and interactions between components, obtained the results of ecosystem components and interactions between ecosystems, the highest percentage on clarify indicators with a gain of 50% in the score position 3; (2) Energy flow, the highest percentage on the clarify indicator with an obtained score 58.3% in the position of score 1; (3) Biogeochemical cycle, the highest percentage obtained for the students who did not answer on the ideate indicator 41.7%, develop 50%, and implement 58.3%; (4) Pollution and environmental preservation the highest percentage on clarifying and ideate indicators with a gain of 50% at the position of score 3, implement with the acquisition of 50% in the position of score 1. This research concluded that students needed to be intensely trained in high-level thinking skills by getting used to using worksheets-based constructivist especially creative problem-solving.